Self-Directed Learning on the Runway to Crafts Entrepreneurship: Achieving Product–Market Fit through Learning Cycles with Self-Management and Self-Control - Katre, Aparna (Artivate: A Journal of Entrepreneurship in the Arts, 2020)
Many artisans practice self-directed learning to gain crafts expertise in non-academic settings. They can apply this skill for crafts entrepreneurship. A preliminary exploratory study supported by three crafts entrepreneurs cases explored their transition from artisanship to entrepreneurship. It begins to address the lack of literature at the nexus of crafts entrepreneurship and self-directed learning. Findings suggest artisans develop their product–market fit and solve business-related issues in self-directed learning cycles, exercising self-management at each step, and self-monitoring the outcomes. With profound implications to promote crafts entrepreneurship in resource-strapped small legacy cities, we present guidance for future research to develop this field.